2004
DOI: 10.1111/j.1365-2141.2004.05005.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic expansion of CD45RA+ CD27 CD28 CCR7 lymphocytes with stable natural killer (NK) receptor expression in NK‐ and T‐cell type lymphoproliferative disease of granular lymphocytes

Abstract: Summary We analysed the cell surface expression of chemokine receptors and natural killer receptors (NKRs) in addition to conventional T‐ and natural killer (NK)‐cell markers in patients with lymphoproliferative disease of granular lymphocytes (LDGL), and compared results between NK‐ and T‐LDGL subgroups. The subjects of this study were 15 LDGL patients: four NK‐LDGL and 11 T‐LDGL [six CD8+ T‐cell receptor (TCR) αβ+, four CD4+ TCRαβ+ and one CD8+ TCRγδ+] cases. Flow cytometric analysis showed that the expandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…However, the CVID LGL–high patients had significantly lower proportions of CD4 + T cells expressing CD45RO than the other CVID patients (see Table 2). Similar to previous observations in patients with LDGL [11], we also found increased proportions of T cells expressing the activation marker HLA‐DR and a trend towards lower proportions of T cells expressing the CC‐chemokine receptor 7 (CCR7) in the CVID LGL–high patients compared to the remaining CVID patients (Table 2). Finally, increased expression of CD57 on circulating T cells has been associated previously with LDGL [7] and has also been observed in CVID.…”
Section: Resultssupporting
confidence: 90%
“…However, the CVID LGL–high patients had significantly lower proportions of CD4 + T cells expressing CD45RO than the other CVID patients (see Table 2). Similar to previous observations in patients with LDGL [11], we also found increased proportions of T cells expressing the activation marker HLA‐DR and a trend towards lower proportions of T cells expressing the CC‐chemokine receptor 7 (CCR7) in the CVID LGL–high patients compared to the remaining CVID patients (Table 2). Finally, increased expression of CD57 on circulating T cells has been associated previously with LDGL [7] and has also been observed in CVID.…”
Section: Resultssupporting
confidence: 90%
“…In previous case series, CNKL cells expressed CXCR1 but not CCR5. 23,24 Our study using DNA microarray methods also demonstrated no significant differences in chemokine receptor mRNA expression levels between CNKL patients and healthy donors. 25 These results in conjunction with our current study suggest that CNKL cells closely resemble the NK cells of healthy donors, while ANKL cells are distinct with regard to their chemokine receptor expression profile.…”
Section: Discussionmentioning
confidence: 58%
“…47,48 The implications of this phenotype remain incompletely defined, but functionally these cells are often unresponsive and do not expand in vitro using traditional T-cell expansion protocols, suggesting either leukemic transformation by an as yet undisclosed genetic mechanism or functional exhaustion due to chronic antigen stimulation. Furthermore, analysis of CD52 expression in NK-LGL also revealed the absence of GPI proteins on putatively clonal cells (Maciejewski, unpublished observations, 2008).…”
Section: Discussionmentioning
confidence: 99%